Kontribusi Self Efficacy dan Grit Terhadap Tingkat Stres Akademik Pada Mahasiswa Yang Mengerjakan Skripsi di Fakultas Ushuluddin dan Humaniora Universitas Islam Negeri Antasari Banjarmasin - Padila, Siti Rizqa (Faculty of Ushuluddin and Humanities, 2024)
This correlational quantitative study aimed to examine the influence of self-efficacy and grit on academic stress among 100 undergraduate students working on their theses. Results indicated that 28% of participants had high self-efficacy, while 72% had moderate levels. Regarding grit, 37% were categorized as high and 63% moderate. Academic stress levels were distributed as 33% high, 64% moderate, and 3% low. T-test analyses revealed that both self-efficacy (t = -3.390, p = 0.001) and grit (t = -3.569, p = 0.001) significantly affect academic stress. Furthermore, the combined effect of self-efficacy and grit on academic stress was significant (F = 31.337, p = 0.000). The study concluded that these two variables significantly influence the academic stress levels of students.